Heat Shock Protein 70 Family in Response to Multiple Abiotic Stresses in the Silkworm - Fang, Shou-Min; Zhang, Qian; Zhang, Yu-Li; Zhang, Gui-Zheng; Zhang, Ze; Yu, Quan-You (Insects (Basel, Switzerland), 2021)
The 70 kDa heat shock proteins play important roles in protecting organisms against environmental stresses, which are divided into stress-inducible forms (HSP70s) and heat shock cognates (HSC70s). In this study, heat shock protein 70 family was identified in the whole genome of the silkworm. Based on the known nomenclature and phylogenetic analysis, four HSP70s and five HSC70s were classified. Relatively, heat shock cognates were more conservative and were constitutively expressed in various tissues of the silkworm larvae. Under thermal (37 °C and 42 °C) and cold (2 °C) stresses, the expressions of HSP70–1, HSP70–2, and HSP70–3 were up-regulated, and the highest induction reached 4147.3, 607.1, and 1987.3 times, respectively. Interestingly, HSC70–1, HSC70–4, and HSC70–5 also showed slight induced expressions in the fat body and/or midgut under thermal stresses. In addition, the expression of HSP70–1 was induced by dichlorvos and phoxim insecticides, while most HSC70 genes were inhibited. The results suggested that stress-inducible forms play more important roles in adaptation to various stresses than HSC70s.